Assessment of a telemetry monitoring system (Movicorde) developed in Cuba - Nurys B. Armas Rojas; Susana Hernández García; Gay Meissimilly González; Juliette Valles Cruz; Mary Eugenia Cartaya Lopez; Eduardo Rivas Estany; Martha Mireya Rivero Varona (ECIMED, 2012)
Introduction The Movicorde system was designed in order to help cardiologists and physiotherapists atexercise training sessions,where constant supervision of relevant parameters is required.Objectives To evaluate the use of Movicorde in high-risk cardiac patients, including the presence of arrhythmias, ST segmentabnormalities and target heart rate.Methods A descriptive, cross-sectional study of 80 high-risk patients who attended the gymnasium of the Institute of Cardiology,from July 2009 through April 2011, in a Cardiac Rehabilitation (CR) program.The measurements taken by Movicordewere compared to those taken by the cardiologists and a data base was created for statistical analyses.Results Sixty two (62) patients had premature ventricular complexes (PVC). The high specificity (99.87 %), sensibility (80,33%)and the 83,42% positive predictive value (VPP) of the system to detect PVC, was described. There was total concordancebetween the equipment and the physicians in 57 patients (71,25%) with respect to ST segment depression.This had a very superior observed value to that expected and showed that the results were representative (p<0,005).Patients who had acute or recent Myocardial Infarction or chronic ischemic heart disease had intermediate total exercise-session duration and their target heart rate had a similar value which was lesser with respect to the rest of thepatients.Conclusions The Movicorde system showed high efficiency for the telemetric analyses of exercise training sessions and its use isrecommended in clinical practice.